Outpatient Service Using an Online Registration System at Rumah Sakit Islam Jakarta Pondok Kopi - Naufal, Hanif Zain; Efkelin, Ria; Yari, Nama Yarwin (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
The advancement of information technology has transformed healthcare services by introducing an online patient registration system, which enhances accessibility and improves service effectiveness. This study aimed to measure the relationship between the quality of the online registration system and the effectiveness of outpatient BPJS services at Rumah Sakit Islam Jakarta Pondok Kopi. A quantitative cross-sectional study design was employed, utilizing purposive non-probability sampling (non-random selection), involving a total of 130 respondents. Data analysis was conducted using SPSS version 27. The results showed that the online system provides good quality, based on the majority of respondents 60%. Meanwhile, the effectiveness of the service shows that 53,8% respondents state it is effective. Furthermore, there is no significant relationship between flexibility and integration dimensions to service effectiveness. However, it is a significant relationship among the reliability, accessibility, and response time dimensions to service effectiveness. This study concluded that the quality of the online registration system significantly influences service effectiveness, particularly in the areas of reliability, accessibility, and response time. To achieve optimal service effectiveness, continuous improvements in system flexibility and integration are essential. It is hoped that this research can contribute to the development of more efficient and responsive healthcare service systems that better meet patient needs.